Le bloc-notes en expansion - autre média, autre discours - Jereczek-Lipinska, Joanna (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2006)
This text falls under research of the discursive analysis as in what one qualifies of the blogoscopy to knowing in the analysis still little developed phenomenon of the blogs. These new media are in full expansion in France. We thus propose to analyze this advent of the new media while starting with simple observation of the language which it generates, while passing by its definition, typology and structure and to arrive finally at the influence and the range that it will be able to have on the political and media speech.
The blog expanding - another media, another discourse